Molecular Cloning and Functional Characterization of a Sterol 3-O-Glucosyltransferase Involved in Biosynthesis of Steroidal Saponins in Trigonella foenum-graecum - Gao, Jianghong; Xu, Yehan; Hua, Congkun; Li, Changfu; Zhang, Yansheng (Frontiers in Plant Science, 2021)
Fenugreek (Trigonella foenum-graecum), a pharmacologically important herb, is widely known for its antidiabetic, hypolipidemic and anticancer effects. The medicinal properties of this herb are accredited to the presence of bioactive steroidal saponins with one or more sugar moieties linked to the C-3 OH position of disogenin or its C25-epimer yamogenin. Despite intensive studies regarding pharmacology and phytochemical profiles of this plant, enzymes and/or genes involved in synthesizing the glycosidic part of fenugreek steroidal saponins are still missing so far. This study reports the molecular cloning and functional characterization of a key sterol-specific glucosyltransferase, designated as TfS3GT2 here, from fenugreek plant. The recombinant TfS3GT2 was purified via expression in Escherichia coli, and biochemical characterization of the recombinant enzyme suggested its role in transferring a glucose group onto the C-3 hydroxyl group of diosgenin or yamogenin. The functional role of TfS3GT2 in the steroidal saponin biosynthesis was also demonstrated by suppressing the gene in the transgenic fenugreek hairy roots via the RNA interference (RNAi) approach. Down-regulation of TfS3GT2 in fenugreek generally led to reduced levels of diosgenin or yamogenin-derived steroidal saponins. Thus, Tf3SGT2 was identified as a steroid-specific UDP-glucose 3-O-glucosyltransferase that appears to be involved in steroidal saponin biosynthesis in T. foenum-graecum.